Mapping Occupational Therapy Practice with Postsecondary Students: A Scoping Review - Karen M. Keptner; Karen McCarthy (Scholarworks @ WMU, 2020)
Background: Legislation supports a role for occupational therapy in postsecondary settings, but this area is not a common practice area and the practice area is not well understood. This scoping review maps current literature of occupational therapists working with students in postsecondary settings in order to inform future research and practice. Method: After identifying included articles, a narrative description of the quantitative studies along with a concept map were completed. A qualitative thematic analysis of the articles was also conducted. Results: Twenty-five articles met the inclusion criteria. Quantitative results describe occupational therapy services as both a direct and indirect service provided through offices of disability services, assistive technology, and supported education programs, among others. The primary population with whom occupational therapists engage with are students with mental illness. Three qualitative themes emerged from the scoping review, including the focus on occupation and skills needed for success, using the campus environment, and campus collaboration. Conclusion: The structure of occupational therapy services varies from location to location and occupational therapists work with various populations of students. Future research needs to support the distinct value of occupational therapy in this practice area, including the scope and outcomes of occupational therapy services with different populations of students.